Faktor-Faktor yang Mempengaruhi Penggunaan Informasi Akuntansi dengan Ketidakpastian Lingkungan Bisnis Sebagai Variabel Moderasi (Pada UKM di Kota Padang) - Mutiara Candra; Rita Rahayu; Denny Yohana (Universitas Batanghari Jambi, 2020)
This study discusses the study and study of accounting knowledge, accounting training, owner education, business scale, company age, and organizational culture of SME owners regarding the use of accounting information in making decisions, using environmental change as a moderating variable. The sample selection method is purposive sampling. This study uses the SmartPLS Ver 2 M3 software to analyze the relationship of accounting, owner education, business scale, company age, and organizational culture to the use of accounting information using the environment as a moderating variable. Testing instruments using reflective constructs and formative constructs is done through testing two research models to see strong moderating variables (Environmental Uncertainty) increasing each variable X to variable Y. The findings of this study are accounting knowledge, accounting training, accounting training, business scale, company age and organizational culture do not influence the use of accounting information, while the owner / manager education influences the use of accounting information. An uncertain business environment cannot moderate the influence of accounting knowledge, accounting training, owner education, business scale, company age and organizational culture on the use of accounting information